Dispersion of platoons of vehicles in Bangkok traffic - Lin, Tyh-ming; Jones, John Hugh; Yordphol Tanaboriboon; Prapansak Buranaprapa; Government o f Republic of China (Bangkok : Asian Institute of Technology, 1981)
The importance of the dispersion factor in the coordination of traffic signa ls has led researchers in Britain, the United States, and Canada to study the dispersion of vehicles as they progress along a street from a traffic signal. The present research describes an investigation to find how platoons o f vehicles released from a traffic signal disperse as they move along the street. Field surveys were carried out at four sites in Metropolitan Bangkok. Parameters observed were the successive two-second flows at the stopline, and at selected points downstream from the stopline after the signal turned green. From this information, flow-time diagrams were constructed to describe the dispersion of platoons of vehicles. These were compared with the flows predicted by Robertson's and Pacey's models. It was concluded that the degree of platoon dispersion at the study sites was significantly less than that suggested by Robertson's parameters. There is evidence in favour of Robertson's and Pacey's methods for the prediction of platoon dispersion.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1981
Keywords: Traffic signs and signals -- Thailand -- Bangkok